The Dehydrogenation Mechanism and Cycling Property of MgH2 Modified by CoB/CNTs Addition. Issue 34 (10th September 2019) - Gao, Shichao; Wang, Xinhua; Liu, Haizhen; He, Ting; Li, Shouquan; Yan, Mi
Abstract: In this paper, the dehydrogenation process of MgH2 +10 wt% CoB/CNTs was studied by X‐ray diffraction (XRD) at various temperatures. The results indicated that a part of CoB/CNTs might react with MgH2 to form the new phase Co3 MgC as the temperature increases from room temperature to 500 °C. Furthermore, it was found that the hydrogen desorption processes of the MgH2 +10 wt% CoB/CNTs and as‐milled MgH2 were controlled by the three‐dimensional phase boundary and the one‐dimensional diffusion kinetic mechanism, respectively. This difference is attributed to the fact that the in‐situ formed Co3 MgC can provide many pathways and act as "hydrogen pumps" for accelerating the hydrogen dissociation and association. Moreover, the cycling property of the MgH2 +10 wt% CoB/CNTs composite was also studied. The hydrogen storage capacity and the hydrogen de/absorption kinetics can remain stable over 6 cycles. MgH2 +10 wt% CoB/CNTs can steadily release about 6.3 wt% of H2 within about 40 min at 300 °C, and hydrogen absorption can be completed rapidly. XRD measurements show that Co3 MgC remains unchanged after 6 cycles, which has positive effect on the cycling stability. Abstract : The CoB/CNTs nanocomposites were prepared and used as catalysts to improve the hydrogen storage properties of MgH2 . During the dehydrogenation, a part of CoB/CNTs might react with MgH2 to form the new phase Co3 MgC. Therefore, the MgH2 +10 wt% CoB/CNTs and as‐milled MgH2 release hydrogen according to different isothermal desorption kinetic model. Moreover, the MgH2 +10 wt% CoB/CNTs exhibits excellent hydrogen desorption/absorption cycling properties.